A Prospective Analysis of Free Flap Monitoring Techniques: Physical Examination, External Doppler, Implantable Doppler, and Tissue Oximetry - Lohman, Robert F.; Langevin, Claude-Jean; Bozkurt, Mehmet; Kundu, Neilendu; Djohan, Risal (Journal of Reconstructive Microsurgery, 2013)
No universally accepted method of flap monitoring exists, and several techniques are in use. Repeated physical examination is most popular and is often supplemented with a handheld, external Doppler, and/or implantable Doppler probes; near-infrared spectroscopy is less commonly used. We investigated the nursing and resident house staff's experience and confidence with physical exam for flap monitoring. Also, a consecutive series of 38 patients with free flaps were monitored using physical examination, external Doppler, implantable arterial and venous Doppler probes, and near-infrared spectroscopy. Five patients developed signs of microvascular complications within 3 days of surgery; all were explored and salvaged. Neither the residents nor the nursing staff were universally trained or experienced in flap monitoring by physical exam. In all patients, changes in the appearance of the flap suggestive of a microvascular complication lagged 30 to 60 minutes after the adjunctive monitoring methods indicated that a problem had occurred. Near-infrared spectroscopy was the first warning sign in four of the five patients. Two patients were explored before thrombosis of the anastomoses occurred. Near-infrared spectroscopy may identify early microvascular complications more reliably than physical examination, external Doppler, or implantable Doppler.
Keywords: monitoring techniques; microsurgery; near infrared spectroscopy; external Doppler; implantable Doppler